The marine food web of the Malpelo Fauna and Flora Sanctuary, Colombia: a structural analysis from a topological approach - Colombo Estupiñán-Montaño; Alberto Sánchez-González; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Carlos J. Polo-Silva (Theoretical Ecology, 2026)

MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Using La2O3/Printex carbon cathode for simultaneous H2O2 generation and synergistic amitriptyline degradation in aqueous matrices - F. Escalona-Durán; C.H.M. Fernandes; G.O.S. Santos; R.J.A. Felisardo; W.R.P. Barros; R. Colombo; M.A. R. Rodrigo; M.R.V. Lanza (Process Safety and Environmental Protection, 2026)

Treatment of veterinary insecticide residues using biomixtures: performance, degradation kinetics, and ecotoxicological assessment - R. C. Pessagno; N. Olié; V. A. Silvani; R. P. Colombo; G. Svartz; A. Iriel (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of two natural astaxanthin products derived from the green microalga Haematococcus lacustris on production parameters and fillet quality of Atlantic salmon (Salmo salar) - Juan A. Manríquez-Hernández; Sean M. Tibbetts; Mark D. Fast; Stacey R. Goldberg; Roumiana Stefanova; Stefanie M. Colombo (Aquaculture International, 2025)

Correction to: Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán‑Montaño; Daniel J. Villalobos‑Ramírez; Felipe Galván‑Magaña; Fernando R. Elorriaga‑Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez‑González; Carlos J. Polo‑Silva; Antonio Delgado‑Huertas (Environmental Biology of Fishes, 2025)

Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán-Montaño; Daniel J. Villalobos-Ramírez; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez-González; Carlos J. Polo-Silva; Antonio Delgado-Huertas (Environmental Biology of Fishes, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evaluating the synergistic effect of UVC/e-H2O2 applied for benzotriazole degradation in water matrices using catalyst-free printex L6 carbon-based gas diffusion electrode - Florymar Escalona-Durán; Carlos H.M. Fernandes; Aline R. Doria; Gessica O.S. Santos; Renata Colombo; Willyam R.P. Barros; Marcos R.V. Lanza (Chemosphere, 2025)

Valorization of corn stover in a single experimental unit: The synergistic effects of steam explosion and semi-continuous subcritical water processing - Francisco D. Vezaro; Suelly R. Hollas; Fernanda A. Colombo; Alex Schulz; Crisleine P. Draszewski; Fernanda de Castilhos; Ederson R. Abaide; Flávio D. Mayer (Science of The Total Environment, 2025)

Factors controlling the water quality of rock glacier springs in European and American mountain ranges - Stefano Brighenti; Nicola Colombo; Thomas Wagner; Michael Pettauer; Nicolas Guyennon; Karl Krainer; Monica Tolotti; Michela Rogora; Luca Paro; Sandra M. Steingruber; Chantal Del Siro; Cristian Scapozza; et al. (Science of The Total Environment, 2024)

LP-38 DockTox: a molecular docking platform for screening small molecules targeting Molecular Initiating Events (MIEs) relevant to liver, kidney and brain adverse events - R. Ortega Vallbona; D. Talavera Cortés; L.E. Carpio Mulas; E. Colombo; A. Roncaglioni; M. Garcia de Lomana; E. Benfenati; D. Gadaleta; R. Gozalbes; E. Serrano Candelas (Toxicology Letters, 2024)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

Marine community trophic structure of Malpelo Island, Colombia from stable isotopes approach - Colombo Estupiñán-Montaño; Carlos J. Polo-Silva; Fernando R. Elorriaga-Verplancken; Alberto Sánchez-González; Manuel J. Zetina-Rejón; Antonio Delgado-Huertas; Jaiver Rojas-Cundumí; Felipe Galván-Magaña (Journal of Marine Systems, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

P25-21: Approach and challenges in the toxicological and allergenicity risk assessment of novel proteins and their sources - I. Nuin Garciarena; O. Albert; P. Colombo; A. Fernández Dumont; M. Laganaro; A. Muñoz González; E. Noriega Fernández; G. Precup; R. Roldán Torres; A. Rossi; E. Ververis; A. Germini; et al. (Toxicology Letters, 2023)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

An innovative approach to the application of electrochemical processes based on the in-situ generation of H2O2 for water treatment - Isaac Sánchez-Montes; Géssica O. S. Santos; Taynara O. Silva; Renata Colombo; Marcos R. V. Lanza (Journal of Cleaner Production, 2023)

Atlantic salmon adapt to low dietary n-3 PUFA and warmer water temperatures by increasing feed intake and expression of n-3 biosynthesis-related transcripts - Stefanie M. Colombo; Suzanne M. Budge; Jennifer R. Hall; Jovana Kornicer; Nolan White (Fish Physiology and Biochemistry, 2023)

Using a novel gas diffusion electrode based on PL6 carbon modified with benzophenone for efficient H2O2 electrogeneration and degradation of ciprofloxacin - Taynara O. Silva; Lorena A. Goulart; Isaac Sánchez-Montes; Géssica O. S. Santos; Renato B. Santos; Renata Colombo; Marcos R. V. Lanza (Chemical Engineering Journal, 2023)

Trophic connectivity between the terrestrial and marine ecosystems of Malpelo Island, Colombia, evaluated through stable isotope analysis - Colombo Estupiñán-Montaño; Manuel J. Zetina-Rejón; Felipe Galván-Magaña; Antonio Delgado-Huertas; Fernando R. Elorriaga-Verplancken; Carlos J. Polo-Silva; Javier Rojas-Cundumí; Daniel J. Villalobos-Ramírez; Alberto Sánchez-González (Marine Biology, 2023)

Disjunct resident population of Melodious Lark Mirafra cheniana discovered in East Africa - Brian W. Finch; R. Stratton Hatfield; Silvia Colombo; Adam S. Kennedy; Marije te Raa; Martin Irestedt; Dawid H. de Swardt; Joe Grosel; Derek Engelbrecht; Callan Cohen; Urban Olsson; Paul F. Donald; et al. (Journal of Ornithology, 2023)
We describe the discovery of a previously unknown population of Melodious Lark Mirafra cheniana from northern Tanzania and southern Kenya, some 2000 km north of what was previously thought to be its northern limit in central Zimbabwe. The identification of this population as M. cheniana is based primarily on analyses of mitochondrial DNA and song. We also clarify relationships within this genus by sequencing material of White-tailed Lark Mirafra albicauda for the first time; although its relationships with other species in the group remain unclear, our analyses clearly show it to be different from M. cheniana in the newly discovered population. The discovery of a population of M. cheniana in East Africa conforms to a known pattern for closely related lark species to have disjunct distributions in southern and eastern Africa.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

Freshwater, Landlocked Grand Lake Strain of Atlantic Salmon (Salmo salar L.) as a Potential Genetic Source of Long Chain Polyunsaturated Fatty Acids Synthesis - Stefanie M. Colombo; Mohamed Emam; Brian C. Peterson; Jennifer R. Hall; Gary Burr; Zeyu Zhang; Matthew L. Rise (Frontiers in Marine Science, 2021)
Selection efforts focused on adaptation to plant-based diets, particularly the ability to synthesize polyunsaturated fatty acids (PUFA), are now emerging in aquaculture. Landlocked salmon (Grand Lake population; GL) may differ from the commercial Saint John River (SJR) strain in terms of PUFA metabolism. The objective of this study was to determine if GL salmon can contribute toward broodstock selection for enhanced PUFA synthesis. Two diets containing either fish oil (FO) or plant-based oil (FO-free) were fed to the SJR and GL strains (∼58 g/fish) for 16 weeks. Growth, liver, and muscle fatty acid (FA) content, and transcript expression of lipid metabolism and inflammation-related genes were evaluated. GL salmon fed the FO diet showed reduced growth compared to SJR salmon (fed either diet); however, GL salmon fed the FO-free diet, growth was not significantly different compared to any group. In liver, SJR salmon fed the FO-free diet had higher levels of n-6 PUFAs (21.9%) compared to GL fed the same diet (15.9%); while GL salmon fed the FO-free diet had higher levels of monounsaturated FAs (48.9%) compared with SJR salmon fed the same diet (35.7%). 20:5n-3 and 22:6n-3 were the same in GL and SJR salmon liver and muscle, respectively, fed the FO-free diet. In liver, GL salmon fed the FO-free diet had higher acac and acly compared to all treatments and had higher fasb compared to both strains fed the FO-diet. GL salmon fed the FO-free diet had higher cd36c and fabp3b in liver compared to GL salmon fed the FO diet and SJR salmon fed either diet. GL salmon fed the FO-free diet had higher lect2a and pgds in liver compared to SJR salmon fed the FO-free diet. In muscle, GL salmon fed the FO-free diet had higher fadsd5 and fadsd6b compared with both strains fed the FO diet. These results suggest there is a genetic basis behind the potential for GL salmon to utilize FO-free diets more efficiently than SJR salmon, with regards to FA metabolism.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Zootechnical performance, biochemical response, and chromaticity in Pacific white shrimp (Litopenaeus vannamei) (Boone, 1931) after the inclusion of lyophilized açaí (Euterpe oleracea) in the diet - Shadai M. Silva; Patricia B. Ramos; Juan R. Buitrago; Thamyres V. N. da Silva; Cleber S. Simião; Grecica M. Colombo; Marcos Schmitz; Marcelo B. Tesser; Carlos Prentice; Wilson Wasielesky; José M. Monserrat (Aquaculture International, 2020)

Reduction of hippocampal IL-6 levels in LPS-injected rats following acute exendin-4 treatment - Luiza P. Géa; Eduarda D. da Rosa; Bruna S. Panizzutti; Érica Z. de Aguiar; Larissa F. de Oliveira; Pamela Ferrari; Angelo Piato; Rosane Gomez; Rafael Colombo; Adriane R. Rosa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

New insights into the trophic ecology of young white sharks (Carcharodon carcharias) in waters off the Baja California Peninsula, Mexico - Elena Tamburin; Fernando R. Elorriaga-Verplancken; Colombo Estupiñan-Montaño; Daniel J. Madigan; Alberto Sánchez-González; Mauricio Hoyos Padilla; Michelle Wcisel; Felipe Galván-Magaña (Marine Biology, 2020)

A novel in vitro methodology to cultivate arbuscular mycorrhizal fungi combining soil and synthetic media - V. A. Silvani; M. Statello; M. V. Scorza; M. Pérgola; R. P. Colombo; A. M. Godeas (Symbiosis, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

Dietary ontogeny of the blue shark, Prionace glauca, based on the analysis of δ13C and δ15N in vertebrae - Colombo Estupiñán-Montaño; Felipe Galván-Magaña; Alberto Sánchez-González; Fernando R. Elorriaga-Verplancken; Antonio Delgado-Huertas; Diego Páez-Rosas (Marine Biology, 2019)

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pumice clasts in cross stratified basalt-dominated sandstones and conglomerates. Characteristics and depositional significance: Huarenchenque Fm (Neuquén, Argentina) - F. Colombo; R. Bargalló; L. A. Spalletti; P. Enrique; I. Queralt (Journal of Iberian Geology, 2019)

You can’t run but you can hide: the negative influence of human presence on mid-sized mammals on an Atlantic island - Isadora Cristina Motta Lessa; Átilla Colombo Ferreguetti; Maja Kajin; Christopher R. Dickman; Helena Godoy Bergallo (Journal of Coastal Conservation, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Paediatric nasopharyngeal cytology: a new diagnostic opportunity? - S. Torretta; P. Marchisio; M. R. Colombo; C. Rosazza; L. Pignataro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

Seasonal course of photosynthetic efficiency in Larix decidua Mill. in response to temperature and change in pigment composition during senescence - M. Galvagno; M. Rossini; M. Migliavacca; E. Cremonese; R. Colombo; U. Morra di Cella (International Journal of Biometeorology, 2013)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)

Molecular Identification of Melanised Non-Sporulating Moulds: A Useful Tool for Studying the Epidemiology of Phaeohyphomycosis - Daniel W. C. L. Santos; Ana Carolina B. Padovan; Analy S. A. Melo; Sarah S. Gonçalves; Viviane R. Azevedo; Marilia M. Ogawa; Tainá Veras Sandes Freitas; Arnaldo L. Colombo (Mycopathologia, 2013)

B1b lymphocyte-derived antibodies control Borrelia hermsii independent of Fcα/μ receptor and in the absence of host cell contact - Matthew J. Colombo; David Abraham; Akira Shibuya; Kishore R. Alugupalli (Immunologic Research, 2011)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Immunostimulatory and cytotoxic activities of Indigofera suffruticosa (Fabaceae) - Flávia C.M. Lopes; Tamara R. Calvo; Lucas L. Colombo; Wagner Vilegas; Iracilda Z. Carlos (Natural Product Research, 2011)

Production of tannase from wood-degrading fungus using as substrate plant residues: purification and characterization - R. M. Ordoñez; I. Colombo; M. R. Alberto; M. I. Isla (World Journal of Microbiology and Biotechnology, 2011)

Calcification in bleached and unbleached Montastraea faveolata: evaluating the role of oxygen and glycerol - M. F. Colombo-Pallotta; A. Rodríguez-Román; R. Iglesias-Prieto (Coral Reefs, 2010)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Detection of Helicobacter pylori, Enterococcus faecalis, and Pseudomonas aeruginosa in the subgingival biofilm of HIV-infected subjects undergoing HAART with chronic periodontitis - L. Souza Gonçalves; R. Souto; A. P. V. Colombo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Agglomerates Containing Pantoprazole Microparticles: Modulating the Drug Release - Renata P. Raffin; Paolo Colombo; Fabio Sonvico; Alessandra Rossi; Denise S. Jornada; Adriana R. Pohlmann; Silvia S. Guterres (AAPS PharmSciTech, 2009)

Novel Platforms for Oral Drug Delivery - P. Colombo; F. Sonvico; G. Colombo; R. Bettini (Pharmaceutical Research, 2009)

Morphological analysis of female gametophyte development in the bel1 stk shp1 shp2 mutant - R. Battaglia; V. Brambilla; L. Colombo (Plant Biosystems, 2008)

Leaf level early assessment of ozone injuries by passive fluorescence and photochemical reflectance index - M. Meroni; V. Picchi; M. Rossini; S. Cogliati; C. Panigada; C. Nali; G. Lorenzini; R. Colombo (International Journal of Remote Sensing, 2008)

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

The barley plastome mutant CL2 affects expression of nuclear and chloroplast housekeeping genes in a cell-age dependent manner - Noemí Colombo; Carola Emanuel; Verónica Lainez; Sara Maldonado; Alberto R. Prina; Thomas Börner (Molecular Genetics and Genomics, 2008)

Influence of vestibular and visual stimulation on split-belt walking - B. Marques; G. Colombo; R. Müller; M. R. Dürsteler; V. Dietz; D. Straumann (Experimental Brain Research, 2007)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Association Between the cfxA Gene and Transposon Tn4555 in Bacteroides distasonis Strains and Other Bacteroides Species - Livia Q. Ferreira; Katia E. S. Avelar; Jessica M. B. D. Vieira; Geraldo R. de Paula; Ana P. V. Colombo; Regina M. C. P. Domingues; Maria C. S. Ferreira (Current Microbiology, 2007)

First lead isotopic data for cinnabar in the Almadén district (Spain): implications for the genesis of the mercury deposits - Pablo Higueras; José Munhá; Roberto Oyarzun; Colombo C. G. Tassinari; Izabel R. Ruiz (Mineralium Deposita, 2005)

Robot-aided neurorehabilitation of the upper extremities - R. Riener; T. Nef; G. Colombo (Medical & Biological Engineering & Computing, 2005)

Single joint perturbation during gait: neuronal control of movement trajectory - V. Dietz; G. Colombo; R. Mller (Experimental Brain Research, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Successful Treatment of an Aspergillus Brain Abscess with Caspofungin: Case Report of a Diabetic Patient Intolerant of Amphotericin B - A. L. Colombo; R. C. Rosas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Identification of Moulds Belonging to the Penicillium Genus using a Polymerase Chain Reaction (PCR-SSCP) Method Followed by 'Computer Assisted' Statistical Analysis of the Electrophoretic Patterns - F. Colombo; L. Vallone; R. Capoferri; I. Dragoni (Veterinary Research Communications, 2003)

Ovule-specific MADS-box proteins have conserved protein-protein interactions in monocot and dicot plants - R. Favaro; R. Immink; V. Ferioli; B. Bernasconi; M. Byzova; G. Angenent; M. Kater; L. Colombo (Molecular Genetics and Genomics, 2002)

Susceptibility profile of vaginal yeast isolates from Brazil - M.A. Ribeiro; R. Dietze; C.R. Paula; D.A. Da Matta; A.L. Colombo (Mycopathologia, 2001)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Exopolysaccharide of Nostoc muscorum (Cyanobacteria) in the aggregation of soil particles - G. Zulpa de Caire; M. Storni de Cano; M. C. Zaccaro de Mulé; R. M. Palma; K. Colombo (Journal of Applied Phycology, 1997)

1,2-Dichloropropane (DCP) toxicity is correlated with DCP-induced glutathione (GSH) depletion and is modulated by factors affecting intracellular GSH - R. Imberti; A. Mapelli; P. Colombo; P. Richelmi; F. Bertè; G. Bellomo (Archives of Toxicology, 1990)

G6PD Pinar del Ro: A new variant discovered in a Cuban family - R. Gonzlez; M. Wade; M. Estrada; E. Svarch; B. Colombo (Biochemical Genetics, 1977)